Accelerating onchocerciasis elimination in humanitarian settings: lessons from South Sudan - Fodjo, Siewe; Jada, S R; Rovarini, J; Bol, Y Y; Carter, J Y; Hadermann, A; Lakwo, T; Colebunders, R (Int Health, 2025)
There is persistent meso- and hyperendemicity of onchocerciasis (river blindness) in South Sudan, a country that has endured armed conflict for many years. In 2018, Amref Health Africa, in collaboration with local communities, the South Sudan Ministry of Health and other stakeholders, initiated some interventions, among which was Innovative Approaches to Reduce the Burden of Disease Caused by Onchocerciasis (IARDO) project. This project implemented several strategies, including identifying areas where onchocerciasis elimination programs need strengthening, switching from annual to biannual community-directed treatment with ivermectin (CDTI), additional ivermectin administration to postpartum women and school children and a community-based 'slash and clear' vector control strategy. These measures resulted in increased CDTI coverage, fewer bites from blackfly vectors and decreased onchocerciasis-related morbidity. The feasibility of these interventions, low cost, national government support and community ownership suggest their long-term sustainability.
DOI: 10.1093/inthealth/ihae051
Keywords: Onchocerciasis; South Sudan